ASEAN economic community: The potential impacts of labour mobility on the economy and construction industry - Hasan, Sharina Farihah; Abdul Rashid, Khairuddin; Ahmad Sarkawi, Azila; Aripin, Srazali; Mohd Fauzi, Puteri Nur Farah Naadia (2016)
In their endeavors to achieve economic integration, the leaders of ASEAN initiated and implemented policies under the so called “ASEAN Economic Community 2015”. The policies relate to almost all sectors of the ASEAN’s economy. In relation to labour mobility, the policy on free movement of skills and unskilled across the 10 member countries of ASEAN may bring economic and non-economic implications to both the host and exporting member countries. However, empirical study on the subject matter is scarce. Consequently, a study employing desk research and a questionnaire survey among respondents from selected member countries of ASEAN was carried out. The findings from the study highlight the potential impacts of labour mobility may have, economically and socially, to both the host and exporting member countries.